Star Trek 30 years - Paramount Pictures Corporation (London Paramount Pictures Corporation, 1996)
With interviews, photographs, over 400 episode and movie descriptions, plus explanations of the Klingon language, collections of Star Trek memorabilia and more
Include Color Illustration
Keywords: Star trek (Television program) -- Star trek, the next generation (Television program) -- Star trek, Deep Space Nine (Television program)